THE EFFECT OF SELF-REGULATED LEARNING AND SELF-EFFICACY ON STUDENT’S SOLVING PROBLEM ABILITY - Sapulete, Lucyana; Laurens, Theresia; Gaspersz, Magy (Jurnal Pendidikan Matematika (JUPITEK), 2023)
Mathematics Problem Solving will give the expected results depending on a person's ability to control and direct his thinking activities (self-regulated learning) as well as his ability to have self confidence in solving problems. This study aimed to determine the effect of self-regulated learning and self-efficacy on problem-solving in social arithmetic material in class 7th graders of Public Junior High School 19 Ambon. The approach used was quantitative, with a sample of 27 students determined by random sampling (randomly). The research instrument used questionnaires and tests. It consisted of the self-regulated learning questionnaire, which 40 items, and the self-efficacy questionnaire 30 items. Data analysis used simple linear regression analysis, multiple linear regression analysis in which there were multiple correlation coefficients, and simultaneous and partial significant hypothesis testing at a significant level = 0.05 with the assistance of SPSS version 26.0. The research results show that : (1) there is no effect of self-regulated learning on problem solving in social arithmetic material 7th graders of Public Junior High School 19 Ambon, (2) there is no effect of self-regulated learning on problem solving in social arithmetic material in 7th graders of Public Junior High School 19 Ambon, (3) there is no effect of self-regulated learning and self-efficacy on problem solving in social arithmetic material in 7th graders of Public Junior High School 19 Ambon The contribution given to these two variables to problem solving is 4.%.